Principal Leadership in Improving Teacher Performance: A Systematic Literature Review - Alief Firmansyah; Kharien Arsylia Lavignes (Universitas Negeri Makassar, 2026)
Principal leadership plays a crucial role in improving teacher performance as a key factor in successful learning in schools. Various studies have examined the relationship between principal leadership and teacher performance, but these findings are scattered and require systematic synthesis. This study aims to analyze principal leadership in improving teacher performance through a Systematic Literature Review (SLR) approach. The research method refers to the PRISMA guidelines, with data sources consisting of national journal articles published between 2016 and 2022 and accessed through Google Scholar. A total of 18 articles that met the inclusion criteria were analyzed using thematic synthesis techniques. The results indicate that principal leadership has a significant influence on improving teacher performance. Transformational leadership, academic and clinical supervision, coaching, and the principal's role as an educator, manager, and motivator have been shown to contribute to improving teacher motivation, discipline, and professionalism. These findings confirm that the quality of principal leadership is a strategic factor in improving teacher performance.